Una mirada a las representaciones cinematográficas de las regiones fronterizas en México - Jean Philippe Clot; Heidi Elizabeth Aguilar Pérez (Les Cahiers ALHIM)
In the south and north of México, the border regions are a stage of complex processes in migration, economic and cultural topics; they give to the region an own character. Contemporary cinema presents stories about the various current issues that characterize this context, which is marked by the boundary between two sovereignties and which constitutes, at the same time, a particular region of traffic flows and encounters. The cinema does not have the same purposes, or the same standards of objectivity that the social sciences, but it’s an important discourse about the society, a representation of reality with a particular language. In this work, we focus in how the Mexican border regions are represented in the movies, with the objective to determine if the cinematographic perspective can enrich the field of academic studies of border dynamics and the phenomenon of migration.